SPORT VA ATROF-MUHITNING OʻZ ARO TA’SIRI: TALABALAR FIKRI - Qaljanov, P.; Qaljanov, R. (SCIENCE and SOCIETY, 2025)
The article broadly interprets the nature of environmental problems and their impact, to a certain extent, on all aspects of human life, including economics, politics, the spiritual life of society, sports, and others.